2019
DOI: 10.1002/bkcs.11834
|View full text |Cite
|
Sign up to set email alerts
|

NaCrO2/Coffee Waste–derived Nitrogen‐doped Carbon Composite as High‐Performance Cathode Material for Sodium Ion Batteries

Abstract: Sodium-ion batteries (NIBs) are promising alternatives to lithium-ion batteries for large-scale energy applications such as energy storage systems, owing to the earth-abundance and low cost of sodium resources. Among layered oxide cathode materials for NIBs, O3-type NaCrO 2 has attracted considerable attention owing to its electrochemically active Cr 3+/4+ , which is unlike that of LiCrO 2 , and potential for carbon coating with a high thermal stability. In this study, we propose a new facile and eco-friendly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…90,91 NaCrO 2 was effectively combined with N-doped CDC to produce a composite with 73% capacity retention after 500 cycles. 92 Guo et al reported an even superior cycling stability (2000 cycles) achieved in advanced cathodes for Na-S batteries, owing to the ultramicropores in the carbon structure which can suppress the formation of polysulfides, responsible for the poor cycling performances of room temperature. 93 Finally, some studies on CDC are notable for future directions focusing on both high performance and device sustainability.…”
Section: Batteries (Lithium and Post-lithium)mentioning
confidence: 99%
“…90,91 NaCrO 2 was effectively combined with N-doped CDC to produce a composite with 73% capacity retention after 500 cycles. 92 Guo et al reported an even superior cycling stability (2000 cycles) achieved in advanced cathodes for Na-S batteries, owing to the ultramicropores in the carbon structure which can suppress the formation of polysulfides, responsible for the poor cycling performances of room temperature. 93 Finally, some studies on CDC are notable for future directions focusing on both high performance and device sustainability.…”
Section: Batteries (Lithium and Post-lithium)mentioning
confidence: 99%
“…Through spectroscopic and microscopic analyses, we demonstrate that the phase separation of Cr 2 O 3 /Al-doped NaCrO 2 is preferred over the formation of Al 2 O 3 /NaCrO 2 or Na-deficient Na 1–2 x Cr 1–2 x Al 2 x O 2 . By combining surface modification and isovalent doping, we show that x Cr 2 O 3 -coated Na­(Cr 1–2 x Al 2 x )­O 2 exhibits unparalleled cyclic stability (Table ), , ,, which cannot be achieved solely by either Cr 2 O 3 coating or Al doping. We investigate the significant improvement in cyclability through synchrotron-based in-situ XRD patterns and changes in chromium concentrations in the electrolyte solution.…”
Section: Introductionmentioning
confidence: 95%
“…O3–Na 0.9 Cr 0.9 Sb 0.05 O 2 retained 70.9% of its initial capacity (111 mAh g –1 ) after 1000 C/D cycles compared to 46.8% retention in pristine NaCrO 2 . Surface modification has also been investigated to improve cyclic stability, ,, in which the surface layer either suppresses side reactions on the cathode surface (e.g., oxidation of chemical species reduced on anodes) or prevents solvent insertion into Na layers. , Carbon was the most popular choice in this category, and various precursors, including citric acid, pitch, coffee waste, and acetylene, have been used for the carbon coating of O3-NaCrO 2 . Among them, pitch-derived carbon-coated O3-NaCrO 2 showed the highest cyclic stability, with approximately 90% of its initial capacity retained after 300 C/D cycles …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation